Transient magneto-convection of water near its maximum density in a cavity with various sink-source arrangements and heat generation - Bindhu, R.; Sivasankaran, Sivanandam; Viswanathan, K.K. (Zielona Góra: Uniwersytet Zielonogórski)
This study emphasizes the transient and steady state analysis on magneto-convection of cold water driven by buoyant force in a chamber with partial heating and cooling combined with internal heat absorption/generation. The considered cavity is of square geometry bounded with different locations of source-sink pairs along its left and right sides. The analysis is confined by placing the source-sink pairs to five different locations traversing in the vertical direction along the boundary. The discretization is implemented using a finite volume approach. QUICK scheme and central difference schemes are utilized to resolve the convective and diffusive terms respectively.
Keywords: maximum density; source-sink location; MHD; free convection; heat generation